Effect of Financial Report Quality and ESG Disclosure on Investment Efficiency in Non-Financial Companies on the Indonesia Stock Exchange 2018-2023 - Auliya, Friska Amanda Fitri; Kholmi, Masiyah; Leniwati, Driana (Ilomata International Journal of Management, 2026)
This study examines the impact of financial reporting quality and Environmental, Social, and Governance (ESG) disclosure on investment efficiency in non-financial firms listed on the Indonesia Stock Exchange (IDX) from 2018 to 2023. Investment efficiency, defined as a firm’s ability to allocate capital to projects with positive Net Present Value (NPV), is increasingly important in Indonesia’s competitive and dynamic market. Despite growing interest, empirical evidence on the joint effects of financial reporting quality and ESG disclosure on investment efficiency remains limited, especially in emerging markets. This research investigates whether transparent financial reporting enhances investment efficiency and whether ESG disclosure constrains it. Using a quantitative method, 56 IDX-listed non-financial firms with consistent annual financial statements and Bloomberg ESG scores were selected via purposive sampling, yielding 336 firm-year observations. Investment efficiency was measured using residuals from the (Biddle et al., 2009) model, financial reporting quality through a modified accrual model, and ESG disclosure via Bloomberg ESG composite scores. Panel regression with bootstrapped standard errors (1,000 replications) was applied for data analysis. The results indicate that financial reporting quality positively affects investment efficiency (p < 0.05), while ESG disclosure negatively affects it (p = 0.05). These findings suggest that high-quality financial reporting improves capital allocation by reducing information asymmetry, whereas excessive or symbolic ESG practices may hinder efficiency if misaligned with strategic objectives. This study contributes to the literature by integrating financial reporting and ESG considerations within a single empirical framework in Southeast Asia, providing insights specific to the Indonesian context.